Development of Refined Electromagnetic Models of Reciprocating Electric Generators with Permanent Magnets - A. B. Menzhinski; A. N. Malashin; P. B. Menzhinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2021)
The analysis of scientific papers devoted to the mathematical description of electric generators of reciprocating motion with permanent magnets demonstrated that the proposed mathematical models of this type of generators are based on the theory of magnetic circuits. Such mathematical models are based on a simplified representation of the magnetic system and the magnetic field in the form of a magnetic circuit with corresponding magnetic conductivities. However, unlike traditional rotary type electric machines, electric generators of reciprocating motion have a number of features, the omission of which in mathematical modeling causes the increase of  the cost of their creation (due to the duration of the design and experimental refinement of the generators). Therefore, at the initial stages of electromagnetic calculation and solving optimization problems, it is necessary to use adequate mathematical models to improve the accuracy of calculations of the parameters of these generators. For this purpose, a mathematical model based on field theory can be used; however, its main drawback is the complexity of its application for solving optimization problems. In this regard, to improve the accuracy of calculations of the parameters of electric generators of reciprocating motion with permanent magnets, it is proposed to use refining coefficients (coefficients of scattering and buckling of the magnetic flux) in mathematical models based on the theory of magnetic circuits. The authors have developed refined electromagnetic models of electric generators of reciprocating motion with permanent magnets, which make it possible to obtain the main parameters of generators at the initial stages of electromagnetic calculation and when solving optimization problems with acceptable accuracy. A distinctive feature of the refined electromagnetic models of generators is the consideration of the scattering and buckling coefficients of the magnetic flux in the magnetic system that change during the simulation.